EQUALITY OF RIGHTS AND OBLIGATIONS OF HUSBAND AND WIFE IN THE KINSHIP SYSTEM: AN INDONESIAN POSITIVE LAW PERSPECTIVE - Nurdiansyah, Putra Pandu Dinata; Izzuddin, Ahmad (Hukum Islam, 2024)
The purpose of this research is to look at how the rights and obligations of husband and wife are applied in the kinship system in Indonesia from the perspective of positive law. This research will also evaluate the extent to which positive law can ensure this equality and find obstacles that hinder it. The research in this article uses normative legal research methodology, it aims to find legal rules, principles, and theories to solve legal problems. The research approach of this article uses a statutory approach. The results show that in forming a fair and harmonious family, couples must have equal rights and obligations. Gender equality in the family sphere can be achieved with a strong commitment from the community, government, and law enforcement agencies. This will greatly benefit all Indonesian people. As a country that is rich in diversity and has various kinship systems such as patrilineal, matrilineal, and parental, the implementation of equal rights and obligations between married couples is what is aimed for in positive law. While each system has its own characteristics, the goal of Indonesian law is to ensure that both husbands and wives can lead equal and fair lives. This is part of a larger effort to create a society that respects and protects the rights of everyone regardless of gender, but it also shows how important it is for the understanding between adat and positive law to achieve the goal of equal rights and obligations between spouses by understanding and applying the principle in various contexts. The implications of this show that equal rights and obligations of husband and wife in the kinship system in Indonesia need an important role from the community, government, and law enforcers in harmony between adat and positive law